Pondok Pesantren dan Penerapan Ukhuwah Islamiyah - Nur Wahib; Misbahus Surur (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2020)
Islamic boarding schools as educational institutions can be used as a model for developing civic concepts in order to fulfill the life skills of citizens. Most of the activities in Islamic boarding schools are building the lives of insan kamil students who have tough faith and the ability to do good deeds that form behavioral values. The development of behavioral values ??in the formation of individual insan kamil is in line with the development of the basic spiritual value structure as an acknowledgment of human dignity which raises the value of social responsibility as part of social values. In the pesantren community, social responsibility is based on the spiritual values ??contained in the concept of ukhuwah Islamiah.